The Roles of MicroRNAs in Breast Cancer - Takahashi, Ryou-u (Cancers (Basel), 2015)
MicroRNAs (miRNAs) constitute a large family of small, approximately 20–22 nucleotide, non-coding RNAs that regulate the expression of target genes, mainly at the post-transcriptional level. Accumulating lines of evidence have indicated that miRNAs play important roles in the maintenance of biological homeostasis and that aberrant expression levels of miRNAs are associated with the onset of many diseases, including cancer. In various cancers, miRNAs play important roles in tumor initiation, drug resistance and metastasis. Recent studies reported that miRNAs could also be secreted via small endosome-derived vesicles called exosomes, which are derived from multiple cell types, including dendritic cells, lymphocytes, and tumor cells. Exosomal miRNAs play an important role in cell-to-cell communication and have been investigated as prognostic and diagnostic biomarkers. In this review, we summarize the major findings related to the functions of miRNAs in breast cancer, which is the most frequent cancer in women, and discuss the potential clinical uses of miRNAs, including their roles as therapeutic targets and diagnostic markers.